Pola Pendidikan Akhlak Anak dalam Keluarga - Azra Pasaribu, Tio Vany; Sultani, Dalmi Iskandar (Jurnal Penelitian Multidisiplin Ilmu, 2024)
The pattern of children's moral education in the family using a literature study approach discusses how a good pattern in educating children. The educational pattern is applied to make children moral according to the guidance of Islamic teachings. The first place out is that children get personality education, self-development as a human being of pious faith. Good and bad children's behavior depends on their upbringing in the family. Making children with good morals requires guidance efforts. That is the pattern of educating with example, compassion, attention, and advice. Instilling the values of Islamic teachings, morals, science, physical, emotional, reasoning, respect for parents, independence. The application of a good pattern can grow and develop children in accordance with Islamic teachings.